Babad Dipanagara A Surakarta Court Poet's Account of the Outbreak of the Java War (1825-30) - Carey, Peter (MBRAS Monographs, 2019)
Prince Dipanagara led the Javanese armies in the Java War (1825-30), 30), the last stand of Java's Old Order against Dutch colonial rule. Some participants immortalised the conflict in verse chronicles known generically as Babad Dipanagara. This book comprises a transliteration of one such Javanese text together with a long introduction, translations into English and Indonesian Malay, and detailed notes.